2018
DOI: 10.29312/remexca.v9i2.1077
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de número de tallos en la producción y calidad de jitomate cultivado en invernadero

Abstract: El jitomate es una de las hortalizas de mayor consumo en todo el mundo, su producción, calidad y tamaño es afectada por condiciones climáticas, necesidades hídricas y manejo de número de tallos. El objetivo de este trabajo fue evaluar la producción de jitomate y algunas variables de calidad, en tres condiciones de manejo, en función de número de tallos. El trabajo se realizó en un invernadero del Colegio de Postgraduados. Se trasplantó el 20 de abril de 2015 con tezontle como sustrato, bajo riego por goteo. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…The Tukey mean comparison test (p≤ 0.01) in Table 2, in which it was ordered based on the variable yield from highest to lowest; shows that for this variable, pruning and driving at two stems per plant produced the highest yield, with the USATX 16117, USATX 9934 and Natalie varieties being the best responders to this management, producing more than 2.3 kg per plant after six harvest weeks These results are contrary to what was found by Mendoza et al, (2018), Arébalo et al, 2018 andby Corella et al, 2013), finding in previous works that varieties pruned to a stem were more yielding.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…The Tukey mean comparison test (p≤ 0.01) in Table 2, in which it was ordered based on the variable yield from highest to lowest; shows that for this variable, pruning and driving at two stems per plant produced the highest yield, with the USATX 16117, USATX 9934 and Natalie varieties being the best responders to this management, producing more than 2.3 kg per plant after six harvest weeks These results are contrary to what was found by Mendoza et al, (2018), Arébalo et al, 2018 andby Corella et al, 2013), finding in previous works that varieties pruned to a stem were more yielding.…”
Section: Resultsmentioning
confidence: 67%
“…Likewise, it helps determine in some commercial types of tomatoes, the number of arms or stems to leave per plant (Vera 2015, cited by Arébalo et al, 2018). Mendoza et al, (2018), in a study carried out to evaluate the effect of pruning one, two and three stems on tomato production, found that single-stemmed plants showed a higher yield, in addition to producing Large fruits in greater percentage.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Side shoots are often pruned, leaving a single stem that reaches more than seven meters long, achieving 15 or more bunches per plant in a single season per year at harvest (3). This production system is relatively new in Mexico and has contributed to the increase in cultivated area, productivity, profitability and quality (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…However, the manipulation of plant density optimizes the intercepted radiation (28,37). A high plant density increases the number of small fruit (20).…”
Section: Introductionmentioning
confidence: 99%
“…Las variedades más utilizadas en estos sistemas de producción son de hábito de crecimiento indeterminado, con densidades de siembra de 2 a 6 plantas m −2 y tallos de más de 7 m de longitud (Sánchez-del Castillo et al 2014). La planta con tallo largo y producción de racimos implican una demanda nutricional alta y consumo de energía para el flujo de nutrientes a las zonas apicales (Mendoza-Pérez et al 2018). En la producción de tomate comercial, el tamaño de los frutos en los cortes iniciales es mayor cuando los tallos son cortos (menor a 3 m) que cuando estos son largos (mayor a 7 m) (Gabriel et al 2016), esto debido a una menor cantidad de agua y nutrientes disponibles para la planta en la parte apical (Arriaga-Frías et al 2016).…”
Section: Introductionunclassified